ASSESSMENT OF THE CREDIT HISTORY OF ENTERPRISES (Polityki Europejskie, Finanse i Marketing)
This is the first of 5 articles describing a research conducted to assess the creditworthiness of enterprises and the impact of such an assessment on the level of lending rates during the crisis that has covered the banking sector in Ukraine. In the framework of this study, it was assumed that the creditworthiness of agrarian enterprises involves the following four factors which are subject to the assessment: the credit history of the enterprise, its financial status, business plan and the adequacy of the security (the subject of the mortgage). This article describes the results of the assessment of the credit history of the enterprise. The aim of the study is to identify the quantitative measure of the correlation between the assessment of the credit history of enterprises and the level of repayment of credit in a crisis of the banking sector, as well as the improvement of methodological approaches to such an assessment.